From 1976 to 2018: reflections on early investigations into the Ebola virus. (21st August 2018) - Piot, Peter; Spencer, Julia
Abstract: In the late 1970s, early investigations into the Ebola virus informed the world's understanding of what was then an unknown disease. One such study, published by Bowen and colleagues in 1978, laid the foundations for future research into its prevention and treatment. However, nearly four decades later, scientific progress had not translated into action on the ground with no approved drugs, no vaccines, and no diagnostic tests available when the 2014–15 outbreak began in West Africa. Encouragingly, it appears that we have learned important lessons from the 2014–2015 outbreak, with a swift and rigorous response to the most recent outbreaks in Équateur Province, Democratic Republic of Congo, including the deployment of a vaccine. Ebola will certainly remain a challenge in the years to come and we as the global health community must ensure that innovative research translates into policy and action on the ground, with the full participation of affected communities.